Targeting the Floating Middle of Pyramid Consumers in Africa: Revisiting Marketing Mix Considerations. Issue 5 (20th October 2022) - Chikweche, Tendai; Lappeman, James; Egan, Paul
Abstract: This research reports on a cross-country based investigation of the floating middle class in Africa demonstrating how their behavior and structure influences the design of marketing mix strategies used by marketers. Questionnaires were used to collect data in ten African cities. Key findings include the importance of branding and core drivers for purchase such as durability, origin, popularity, affordability, and a unique circle of quality variables. Innovative adaptations for pricing, distribution and marketing communications are outlined to assist marketers develop appropriate context relevant strategies to target the floating middle class. The discussion also outlines theoretical and practical implications.